Dampak Kepatuhan Syariah terhadap Kinerja Keuangan Bank Syariah: Studi Kasus pada Struktur Pengawasan dan Manajemen Risiko - Sunardi Selamat (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Shariah compliance is important for Islamic banks because it is one of the factors that determines their financial performance. This study aims to analyze the impact of shariah compliance on the financial performance of Islamic banks, with a case study on the supervisory structure and risk management. This study uses a case study method with three Islamic banks in Indonesia as the object of study. The data used in this study is secondary data obtained from the annual reports of these Islamic banks. The results of the study show that shariah compliance has a positive impact on the financial performance of Islamic banks. This impact can be seen from several aspects, including: Profitability: Islamic banks with high shariah compliance have better profitability than those with low shariah compliance, Liquidity: Islamic banks with high shariah compliance have better liquidity than those with low shariah compliance, Risk: Islamic banks with high shariah compliance have lower risk than those with low shariah compliance. Shariah compliance also has a positive impact on the supervisory structure and risk management of Islamic banks. This impact can be seen from several things, including: Supervisory structure: Shariah compliance can enhance the role of the Shari'ah Supervisory Board (SSB) in overseeing the business activities of Islamic banks, Risk management: Shariah compliance can enhance the role of the risk unit in managing risks related to shariah compliance. Based on the results of this study, it can be concluded that shariah compliance is an important factor that determines the financial performance of Islamic banks. Strong supervisory and risk management structures can help Islamic banks to improve shariah compliance and, ultimately, improve their financial performance.